2018
DOI: 10.5387/fms.2018-15
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 induces drug resistance in renal cell carcinoma

Abstract: Metastatic renal cell carcinoma (mRCC) is a tumor entity with poor prognosis due to limited therapy options. Tyrosine kinase inhibitors (TKIs), the novel targeted agents have been used for the treatment of mRCC and have shown efficacy. Interferon (IFN)-α is also one of the most frequently used agents in immunotherapy. However, drug resistance needs to be overcome to achieve a sufficiently positive effect. Interleukin-6 (IL-6), which induce suppressor of cytokine signaling-3 (SOCS3) expression, is one of the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 62 publications
(60 reference statements)
0
35
0
2
Order By: Relevance
“…In contrast, STAT3 becomes hyperactivated in the majority of human cancers and is generally associated with poor clinical prognosis [ 8 ]. Therefore, it is not surprising that STAT3 signaling pathway has long been recognized as a potential therapeutic target for cancer therapy owing to their roles in tumor formation, metastasis and drug resistance [ 9 12 ]. Moreover, accumulating evidence reveals that STAT3 hyperactivation can mediate tumor-induced immunosuppression at many levels [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, STAT3 becomes hyperactivated in the majority of human cancers and is generally associated with poor clinical prognosis [ 8 ]. Therefore, it is not surprising that STAT3 signaling pathway has long been recognized as a potential therapeutic target for cancer therapy owing to their roles in tumor formation, metastasis and drug resistance [ 9 12 ]. Moreover, accumulating evidence reveals that STAT3 hyperactivation can mediate tumor-induced immunosuppression at many levels [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, IL-6 is a potential target in cancer therapy [41,42]. Ishibashi et al reported that IL-6 suppresses the expression of the cytokine signaling-3 (SOCS3) gene and is associated with poor prognosis of kidney cancer patients [43]. Next, we checked if the selected miRNAs and mRNAs were common between the TCGA and GEO datasets.…”
Section: Resultsmentioning
confidence: 99%
“…This compound is a humanized monoclonal antibody (MoAb) targeting interleukin-6 receptor (IL-6R). Pharmacology, pharmacokinetics, clinical efficacy, safety, and role of tocilizumab in rheumatoid arthritis (RA) are well-established [58] and possibly due also to its effect on the AKT/mTOR pathway [59]. Tocilizumab has also been approved for the treatment of the cytokine storm associated with cancer immunotherapy [60] or, more often, with CAR-T therapy [61,62].…”
Section: Immunomodulatory Medications Tocilizumabmentioning
confidence: 99%